The Dark Side of the Affective Profiles - Danilo Garcia; Lillemor Adrianson; Trevor Archer; Patricia Rosenberg (SAGE Open, 2015)
The affective profiles model is based on the combination of individuals’ experience of high/low positive affect and high/low negative affect: self-fulfilling, high affective, low affective, and self-destructive. We used the profiles as the backdrop for the investigation of individual differences in malevolent character traits (i.e., the Dark Triad: psychopathy, Machiavellianism, and narcissism). A total of 1,000 participants (age: M = 31.50 SD = 10.27, 667 males and 333 females), recruited through Amazons’ Mechanical Turk (MTurk), responded to the Positive Affect Negative Affect Schedule and the Dark Triad Dirty Dozen. Individuals with a high affective profile reported higher degree of narcissism than those with any other profile, and together with individuals with a self-destructive profile, also higher degree of Machiavellianism and psychopathy than individuals with a low affective and self-fulfilling profile. Males scored higher in Machiavellianism and psychopathy. Together with earlier findings, our results show that while individuals in both the self-fulfilling and high affective profiles are extrovert and self-directed, only those in the high affective profile express an immature and malevolent character (i.e., high levels of all Dark Triad traits). Conversely, individuals in the self-fulfilling profile have earlier reported higher levels of cooperativeness and faith. More importantly, the unique association between high levels of positive emotions and narcissism and the unified association between negative emotions to both psychopathy and Machiavellianism imply a dyad rather than a triad of malevolent character traits.